Distraction lengthening of the proximal phalanx in distal thumb amputations - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2015)
Objective: Thumb amputation is a major cause of hand dysfunction, and the treatment for distal thumb amputations remains controversial. Although finger reconstruction methods using distraction lengthening are known to restore finger length and function, we found no reports in the literature regarding phalangeal lengthening in thumb amputations. We aimed to evaluate proximal phalangeal lengthening in thumb amputations at or near the interphalangeal (IP) joint. Methods: We retrospectively evaluated patients who had undergone distraction lengthening of the proximal phalanx of the thumb. All patients underwent osteotomy, either during the initial procedure or as a second-stage procedure. Distraction began 10 days after osteotomy with the use of an external fixator that remained in place until ossification of the gap occurred without bone grafting. Patients were evaluated using the QuickDASH score. Results: Fourteen patients with a mean age of 27 years and a mean follow-up period of 7 years were enrolled. The mean phalangeal lengthening achieved was 20 mm. Ossification occurred at all distraction sites, and the fixators were maintained for a mean of 85 days. The mean healing index was 42.5 days/cm. All 14 patients achieved the desired amount of phalangeal lengthening without major complications such as nonunion, premature union, or gross infection. Conclusion: For reconstruction in cases of distal thumb amputations, distraction lengthening of the proximal phalanx can be used to improve absolute length, web space, and grip distance. The technique is safe and effective, improves functionality/cosmesis, and offers a low complication risk.
Keywords: Distraction lengthening; phalangeal lengthening; thumb amputation; thumb lengthening; thumb reconstruction; RECONSTRUCTION